2013
DOI: 10.3945/ajcn.112.054353
|View full text |Cite
|
Sign up to set email alerts
|

Associations of noniodized salt and thyroid nodule among the Chinese population: a large cross-sectional study

Abstract: These findings indicate that low iodine intake may increase the risk of thyroid nodule in a Chinese population, particularly in women. Hence, the Universal Salt Iodization program may be indispensable for a coastal Chinese population such as that living in Hangzhou. This trial was registered at clinicaltrials.gov as NCT01838629.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
5
40
3
Order By: Relevance
“…Recently, a cross-sectional study on the relationship between non-iodized salt and thyroid nodules conducted in Hangzhou (a foreland city in China) found a significant correlation between low urine iodine concentration and high thyroid nodules prevalence. However, in contrast to our findings, the Hangzhou study did not find a significant relationship between high and excess iodine intake and thyroid nodules [30]. In that study, the excessive iodine intake population selection didn't depend on the MUI of the population, but depended on the individual urine iodine concentration [30].…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, a cross-sectional study on the relationship between non-iodized salt and thyroid nodules conducted in Hangzhou (a foreland city in China) found a significant correlation between low urine iodine concentration and high thyroid nodules prevalence. However, in contrast to our findings, the Hangzhou study did not find a significant relationship between high and excess iodine intake and thyroid nodules [30]. In that study, the excessive iodine intake population selection didn't depend on the MUI of the population, but depended on the individual urine iodine concentration [30].…”
Section: Discussioncontrasting
confidence: 99%
“…A study from Hangzhou, China, showed that subjects with low UIC had an increased risk of thyroid nodules. 27 Interestingly, our findings revealed no significant differences in the prevalence of thyroid nodules, autoimmune thyroiditis or subclinical hyperthyroidism across different iodine nutritional levels. With longer follow-up periods and a larger sample size of subjects, these differences may have been statistically significant.…”
Section: Discussionmentioning
confidence: 79%
“…The application of the equation above gave 1.0 and 1.3 lg/kg/day, respectively. A recent report from China states that 24 and 35 % of the men and women, respectively, had thyroid nodules, an indicator of insufficient iodine intake [41] in areas where table salt was not iodized, suggesting that iodine intake was insufficient among general population even in coastal areas in China. Similarly, a publication on population in two regions in Nepal [42] reported low iodine intake levels; the GM levels were 3.14 and 2.62 lg/kg/ day for men and women in one region, and 3.02 and 2.07 lg/kg/day in the other when body weights of 65 and 53 kg were assumed for body weights of men and women, respectively [38].…”
Section: Discussionmentioning
confidence: 97%